Replicating Skull Base Anatomy With 3D Technologies: A Comparative Study Using 3D-scanned and 3D-printed Models of the Temporal Bone. Issue 3 (March 2020) - Chae, Ricky; Sharon, Jeffrey D.; Kournoutas, Ioannis; Ovunc, Sinem S.; Wang, Minghao; Abla, Adib A.; El-Sayed, Ivan H.; Rubio, Roberto Rodriguez
Abstract : Hypothesis: 3D technologies, including structured light scanning (SLS), microcomputed tomography (micro-CT), and 3D printing, are valuable tools for reconstructing temporal bone (TB) models with high anatomical fidelity and cost-efficiency. Background: Operations involving TB require intimate knowledge of neuroanatomical structures—a demand that is currently met through dissection of limited cadaveric resources. We aimed to document the volumetric reconstruction of TB models using 3D technologies and quantitatively assess their anatomical fidelity. Methods: In the primary analysis, 14 anatomical characteristics of right-side TB from 10 dry skulls were measured. Each skull was 3D-scanned using SLS to generate virtual models, which were measured using mesh processing software. Metrics were analyzed using mean absolute differences and one-sample t tests with Bonferroni correction. In the secondary analysis, an individualized right-side TB specimen (TBi) was 3D-scanned using SLS and micro-CT, and 3D-printed on a stereolithography printer. Measurements of each virtual and 3D-printed model were compared to measurements of TBi. Results: Significant differences between the physical skulls and virtual models were observed for 11 of 14 parameters ( p  < 0.0036), with the greatest mean difference in the length of petrous ridge (2.85 mm) and smallest difference in the diameter of stylomastoid foramen (0.67 mm). In the secondary analysis, greater mean differences were observed between TBi and virtual models than between TBi and 3D-printed models. Conclusion: For the first time, our study provides quantitative measurements of TB anatomy to demonstrate that 3D technologies can facilitate individualized and highly accurate reconstructions of TB, which may benefit anatomy education, clinical training, and preoperative planning. Abstract : Supplemental Digital Content is available in the text